CSC430 - Computer Programming and Applications / College of Computing, Informatics and Media - UiTM, College of Computing, Informatics and Media (Universiti Teknologi MARA (UiTM), 2022)
This course is designed for students to study engineering programming. Fundamental concepts and principles of the chosen computer programming language are covered in this course. Considerable emphasis is placed on the understanding and application of computer programming.